Dystocia in Swedish beef cattle : effects of different scoring systems on the genetic evaluation - Nilsson, Filip (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2019)
In Swedish beef cattle breeding, the genetic evaluation comprises calving traits, carcass traits and growth traits. For the calving traits stillbirth, birth weight and dystocia severity grade are recorded. The genetic evaluation for dystocia is divided into four traits; maternal and direct effect when the mother is a primiparous cow, and maternal and direct effect when the mother is a multiparous cow. The system for reporting the grade of dystocia changed in May 2012 from a three-graded scale to a four-graded scale. The distribution of the dystocia grades became mark-edly different, which affected the breeding values in a way that several extremely low values have occurred. This report examines different genetic evaluations with alternative normal scores in-stead of the old scores corrected for heterogeneous variance. Also some genetic correla-tions that had been put to zero to avoid extremely low breeding values were again added to the genetic evaluation to examine their effect on the breeding values. In the current reporting system there are examples of negative breeding values, while in the old reporting system the breeding values were not that extreme. The breeding values seem to be more normally distributed when using the transformed normal scores com-pared to the old scores. There are also less extremely low breeding values. When adding the genetic correlations between the traits, the breeding values changed a little bit. Overall the results indicate that the genetic evaluation is more influenced by changes in the scores system than by the genetic correlation.